Potential strategies to reduce inappropriate prescribing and dispensing of antimicrobials in Bangladesh building on the experiences in other developing countries (Bangladesh Journal of Medical Science, 2021)
Abstract not availableBangladesh Journal of Medical Science Vol.20(4) 2021 p.700-706